Realistic mathematics education: Mathematics e-modules in improving student learning outcomes - Palinussa, Anderson Leonardo; Tupamahu, Pieter Zakarias; Sabandar, Vederico Pitsalitz; Makaruku, Yulian Hanny; Sabandar, Jozua (IKIP Siliwangi and I-MES, 2025)
Realistic Mathematics Education (RME) has gradually influenced the development of mathematics learning worldwide, including in Indonesia. Through the implementation and development of online-based 21st-century education, RME is increasingly proving itself as an effective approach to improving the quality of mathematics teaching and student learning. Learning using the RME approach based on the e-module System aims to become a real learning experience for education and students in implementing mathematical concepts into web-based software systems. The type of research used is pseudo-experimental research with a population in this study of 3 schools, and the number of samples is 147 students. Hypothesis testing was carried out with the N-gain test on the experimental class and control class and the Linear Regression Analysis Test to determine the effect of Gender on improving the learning outcomes of the experimental class. The results of this study show that: 1) There is a difference in the improvement of learning outcomes of classes taught with the RME approach based on the e-module System with conventional learning models; 2) There is no significant difference in the improvement of learning outcomes of students taught using the RME approach based on the E-Module System based on gender characteristics; 3) Gender only contributes 0.1% to the improvement of learning outcomes while 99.9% of other factors.